When the transmission of culture is child's play. - Mark Nielsen; Jessica Cucchiaro; Jumana Mohamedally (PLoS ONE)
Background Humans frequently engage in arbitrary, conventional behavior whose primary purpose is to identify with cultural in-groups. The propensity for doing so is established early in human ontogeny as children become progressively enmeshed in their own cultural milieu. This is exemplified by their habitual replication of causally redundant actions shown to them by adults. Yet children seemingly ignore such actions shown to them by peers. How then does culture get transmitted intra-generationally? Here we suggest the answer might be 'in play'. Principal findings Using a diffusion chain design preschoolers first watched an adult retrieve a toy from a novel apparatus using a series of actions, some of which were obviously redundant. These children could then show another child how to open the apparatus, who in turn could show a third child. When the adult modeled the actions in a playful manner they were retained down to the third child at higher rates than when the adult seeded them in a functionally oriented way. Conclusions Our results draw attention to the possibility that play might serve a critical function in the transmission of human culture by providing a mechanism for arbitrary ideas to spread between children.